Familial pseudohyperkalemia in blood donors: a novel mutation with implications for transfusion practice. Issue 12 (19th June 2014) - Bawazir, Waleed M.; Flatt, Joanna F.; Wallis, Jonathan P.; Rendon, Augusto; Cardigan, Rebecca A.; New, Helen V.; Wiltshire, Michael; Page, Lizanne; Chapman, Catherine E.; Stewart, Gordon W.; Bruce, Lesley J.
<x xml:space="preserve">Abstract</x> Background Familial pseudohyperkalemia (FP) is a dominantly inherited condition in which red blood cells (RBCs) have an increased cold‐induced permeability to monovalent cations. Potassium leaks into the supernatant of all stored blood with time, but FP RBCs leak potassium more rapidly. We investigated two unrelated blood donors whose RBC donations demonstrated unexpectedly high potassium after 5 and 6 days' storage. We matched the observed pattern of RBC cation leak to a previously recognized family with FP (FP‐Cardiff) and investigated the likely cause with targeted DNA analysis. Study Design and Methods Cation leakage from the donor RBCs and from standard donor units was measured. DNA analysis of donors and family members with FP‐Cardiff was performed. Allele frequencies were obtained from human variation databases. Results Both implicated donors were found to have increased cold‐induced potassium leak identical in pattern to affected members of the family with FP‐Cardiff. We found a heterozygous substitution Arg723Gln in the ATP‐binding cassette, Subfamily B, Member 6 protein that segregated with FP in the Cardiff family and was also present in both blood donors. Arg723Gln is listed in human variation databases with an allele frequency of approximately 1:1000. Conclusions We describe a novel FP mutation that may affect 1:500 European blood donors and causes rapid loss of potassium from stored RBCs. This finding has implications for neonates and infants receiving large‐volume RBC transfusions. Genomic screening of donors could be used to identify donors with this mutation and potentially improve the quality and safety of donor units.